Benzo[c]phenanthrene derivatives: Synthesis, optical properties and cytotoxic activity - Guédouar, Habiba; Aloui, Faouzi; Ben hassine, Bechir (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
A new benzo[c]phenanthrene ketone has been synthesized through Heck coupling and oxidative photocyclization. The optical properties of the target tetracyclic system were also investigated by UV-visible absorption and photoluminescence spectroscopy and an emission in the visible region was observed. The tetracyclic ketone has been reacted with primary amines in the presence of Lewis acid followed by NaBH4 reduction to provide new polyaromatic secondary amines in good yields and purity. All the synthesized new compounds were identified and characterized through a combination of nuclear magnetic resonance spectroscopy and mass spectrometric methods. The cytotoxic activity of all pure benzo[c]phenanthrene derivatives has been evaluated against Hep-2 cell line using (MTT) coloriÂmetric assay.